2018
DOI: 10.1007/s11084-018-9558-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Peptide Standards for Use in Model Prebiotic Reactions

Abstract: A one-pot method was developed for the preparation of a series of β-alanine standards of moderate size (2 to ≥12 residues) for studies concerning the prebiotic origins of peptides. The one-pot synthesis involved two sequential reactions: (1) dry-down self-condensation of β-alanine methyl ester, yielding β-alanine peptide methyl ester oligomers, and (2) subsequent hydrolysis of β-alanine peptide methyl ester oligomers, producing a series of β-alanine peptide standards. These standards were then spiked into a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The formation of β-peptides under model prebiotic conditions was also demonstrated. For instance, β-glutamic acid readily oligomerizes in the presence of the water-soluble carbodiimide 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide (EDAC) at −20 °C . In a subsequent study, the oligomerization of α-amino acids was compared with that of β-amino acids in aqueous solution using two different condensing agents .…”
Section: Alternative Proto-peptidesmentioning
confidence: 99%
“…The formation of β-peptides under model prebiotic conditions was also demonstrated. For instance, β-glutamic acid readily oligomerizes in the presence of the water-soluble carbodiimide 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide (EDAC) at −20 °C . In a subsequent study, the oligomerization of α-amino acids was compared with that of β-amino acids in aqueous solution using two different condensing agents .…”
Section: Alternative Proto-peptidesmentioning
confidence: 99%
“…Each carbon-carbon bond within the amino acid backbone permits rotation that increases the flexibility of a peptide chain [75][76][77] (also see Figure 3). But while the lack of backbone rigidity has long been noted as one simple reason why natural selection would favor α-amino acids for the genetic code [10], synthetic biology demonstrates that β-amino acid peptide structures are possible [78][79][80]. Thus, arguments for the exclusion of β-, γ-, and δ-amino acids from the genetic code again resemble those for homochirality: a more robust explanation than strict biophysical constraint is evolutionary optimization.…”
Section: α-Amino Acids Versus Longer Backbonesmentioning
confidence: 99%
“…Several reports have discussed the formation of peptides containing beta amino acids in model abiotic reactions [54][55][56][57][58][59][60][61][62][63]. For instance, it has been shown that β-alanine is polymerized into β-peptides during wet-dry cycling in the presence of glycerol and sodium biocarbonate [54].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have discussed the formation of peptides containing beta amino acids in model abiotic reactions [54][55][56][57][58][59][60][61][62][63]. For instance, it has been shown that β-alanine is polymerized into β-peptides during wet-dry cycling in the presence of glycerol and sodium biocarbonate [54]. In addition, polymerization was demonstrated with beta amino acids activated with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDAC) [55,56] and by the methyl ester forms of beta amino acids [54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation